Protective effect of sex steroid hormones on morphological and cellular outcomes after neonatal hypoxia-ischemia: A meta-analysis of preclinical studies. (February 2023) - Durán-Carabali, L.E.; Da Silva, J.L.; Colucci, A.C.M.; Netto, C.A.; De Fraga, L.S.
Abstract: Sex steroid hormones play an important role in fetal development, brain functioning and neuronal protection. Growing evidence highlights the positive effects of these hormones against brain damage induced by neonatal hypoxia-ischemia (HI). This systematic review with meta-analysis aims to verify the efficacy of sex steroid hormones in preventing HI-induced brain damage in rodent models. The protocol was registered at PROSPERO and a total of 22 articles were included. Moderate to large effects were observed in HI animals treated with sex steroid hormones in reducing cerebral infarction size and cell death, increasing neuronal survival, and mitigating neuroinflammatory responses and astrocyte reactivity. A small effect was evidenced for cognitive function, but no significant effect for motor function; moreover, a high degree of heterogeneity was observed. In summary, data suggest that sex steroid hormones, such as progesterone and 17β estradiol, improve morphological and cellular outcomes following neonatal HI. Further research is paramount to examine neurological function during HI recovery and standardization of methodological aspects is imperative to reduce the risk of spurious findings. Highlights: Morphological parameters can benefit from sex steroid hormonal intervention after neonatal HI. Sex steroid hormones cause protective effects associated to neuronal ang glial function that counteract HI-induced damage. Small overall effect was found for cognitive and motor function. Sex differences related to steroid hormone treatment following neonatal HI remain poorly understood.